1997
DOI: 10.1021/jp963792l
|View full text |Cite
|
Sign up to set email alerts
|

EXAFS and ab Initio Molecular Orbital Studies on the Structure of Solvated Silver(I) Ions

Abstract: Structure parameters of solvated silver(I) ions in eight neat solvents were determined by extended X-ray absorption fine structure spectroscopy. The coordination geometry of the solvated silver(I) ion is four-coordinate tetrahedral at the Ag−O bond distances of 239 pm in trimethylphosphate, 239 pm in N,N-dimethylformamide, 238 pm in 1,1,3,3-tetramethylurea, and 238 pm in dimethyl sulfoxide as oxygen-donating solvents, and at the Ag−N bond distances of 229 pm in acetonitrile, 230 pm in 2-methylpyridine, 229 pm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
54
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(57 citation statements)
references
References 43 publications
3
54
0
Order By: Relevance
“…The reevaluated value (40.4) of TMU is larger than that reported previously, and means that the electron-donating property of TMU is very large in comparison with DMF and DMSO. The solvation structures of metal ions have been previously determined in TMU, [14][15][16]19,20 and the solvation number in bulky TMU found to be smaller than those in other smaller solvents because of the steric repulsion between the bound TMU molecules in the first solvation shell. In addition to the bulkiness of the TMU molecule, its strong donating ability contributes to reduction of the solvation number because of the electronic repulsions on the metal ion.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reevaluated value (40.4) of TMU is larger than that reported previously, and means that the electron-donating property of TMU is very large in comparison with DMF and DMSO. The solvation structures of metal ions have been previously determined in TMU, [14][15][16]19,20 and the solvation number in bulky TMU found to be smaller than those in other smaller solvents because of the steric repulsion between the bound TMU molecules in the first solvation shell. In addition to the bulkiness of the TMU molecule, its strong donating ability contributes to reduction of the solvation number because of the electronic repulsions on the metal ion.…”
Section: Resultsmentioning
confidence: 99%
“…Although the DN value of FA (24) is slightly smaller than that of DMF (26.6), such a comparison must be carefully done because the value of FA is estimated by a different method from that used for DMF. 6,7,12 Similarly to the case of FA, although the chemical characteristics of metal ions in TMU such as the solvation structure are compared with those in the other amides on the basis of DN values, [14][15][16] it should be noted that they are not determined by the same experimental method. It has been reported that the solvation number of the metal ion is variable from 4 to 6 according to the ionic size and charge in TMU with the bulky molecular structure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, the Ag + ion tends to adopt a tetrahedral coordination in neat solvents [1][2][3][4], where the ligand-ligand repulsion is minimized by the symmetrical arrangement of the ligands. However, the 5s and 4d z 2 orbitals of Ag + occasionally undergo the hybridization [11][12][13], which modifies the electron-density distribution by generating two areas of low electron density along the z-axis.…”
Section: Preceding Studies Of Ag + (Ch 3 Oh) Nmentioning
confidence: 99%
“…Nonetheless, four-coordinated geometries have been exclusively observed for Ag(I) in neat solvents [1][2][3][4]. Earlier studies of Ag(I) in aqueous solution showed that the Ag(I) ion binds four H 2 O molecules in a regular tetrahedral geometry [5][6][7].…”
Section: Introductionmentioning
confidence: 99%